(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Testing is not debugging. The procedure comprising of all lifecycle exercises that fulfill determined necessities, to show that they are fit for reason and to identify the imperfections is called as Testing. To discover the mistakes and errors software testing is essential procedure. The point testing a web application comprises of implementing the application utilizing mixes of info and result to uncover failures. There are various testing procedures which serve unique purposes however it is difficult to track down and right all the inaccuracies. Software testing on an online application is accomplished with the goal that to meet the customer’s requirements the performance, quality of the application remains intact. Through this paper, to analyze the load the website can carry up to which extent, the stress is made on the application part. The application is laid in a great deal of regularity frequently to shattering juncture such as the steadiness of the website maybe possibly deemed. This is completed by affixing the code of JavaScript to the application page whose tension requires to be tested. To use the results in future for further studies by the developer or the tester they are stored in a database.